Pengembangan Model Komunikasi Terapeutik Melalui Pelatihan Induktif 3 H (Head-Hand-Heart) Berbasis Kesantunan Berbahasa Pada Mahasiswa Keperawatan - Rohayati, - (2023)
Currently therapeutic communication becomes an important object in health research. Patient complaints about the communication behavior of nurses who are considered less polite are still being felt. Therefore, therapeutic communication skills need to be improved. The use of language politeness can provide comfort and harmony in communicating and it is recommended that nursing students need modeling of communication. Efforts made to improve communication skills are providing language politeness-based training. The purpose of this research is to describe the language politeness profile of nursing students, to design a Therapeutic Communication Model Through Inductive 3H (Head-Hand-Heart) Training Based on Language Politeness to nursing students (Model KTMPI-3H-BKB), to produce the KTMPI-3H-BKB Model, and describe the responses of KTMPI-3H-BKB Model training participants. The final product of this research is the KTMPI-3H-BKB Model. This model provides guidelines for therapeutic communication using Leech's politeness principles, namely six politeness maxims in each phase of therapeutic communication. This research is a qualitative research using R&D method. Data collection techniques were carried out by interviews, observation, questionnaires, while quantitatively by conducting experiments. The results showed that the KTMPI-3H-BKB Model was effectively used to improve the therapeutic communication skills of nursing students. The development of the initial and final models lies in the role of the peer tutor during the simulation or practice of communicating. Model Participants Through Inductive 3H (Head-Hand-Heart) Training Based on Politeness Speaking to nursing students (Model KTMPI-3H-BKB) provides a response to training on the KTMPI-3H-BKB model that is fun, positive, no negative responses, as often as possible, useful , and easy.